Assessing How Hybrid Learning Shapes Academic Achievement: Evidence of Communication-Mediated Effects in Higher Education - Parinsi, Welimas Kristina; Musa, Anugrah Dwi Lestari; Musa, Kartika Septiary Pratiwi (Malaqbi Publisher, 2025)
This research explores the effect of hybrid learning on students' Grade Point Average (GPA) in the Management Study Program at Makassar State University, with interpersonal communication as an intervening variable. The Covid-19 pandemic has forced educational institutions to adapt to new learning methods, combining face-to-face and online learning. This research aims to evaluate the effectiveness of the hybrid learning model in increasing GPA and identify the role of interpersonal communication in this process. Through a quantitative approach with descriptive methods, data were collected using a questionnaire distributed to active students from the 2021 to 2024 classes. The research results show that hybrid learning significantly increases students' GPA, and the effectiveness of interpersonal communication is proven to mediate the relationship between hybrid learning and increasing GPA. These findings emphasize the importance of clear and responsive communication in supporting the learning process, as well as encouraging the development of better communication strategies to achieve optimal academic results.